Labor market dynamics in Romania during a period of economic liberalization - Benoît Dostie; David E. Sahn (Institute for the Study of Labor (IZA), 2006)
In this paper, we estimate a model of labor market dynamics among individuals in Romania using panel data for three years, 1994 to 1996. Our motivation is to gain insight into the functioning of the labor market and how workers are coping during this period of economic liberalization and transformation that began in 1990. Our models of labor market transitions for men and women examine changing movements in and out of employment, unemployment, and self-employment, and incorporate specific features of the Romanian labor market, such as the social safety net. We take into account demographic characteristics, state dependence, and individual unobserved heterogeneity by modeling the employment transitions with a dynamic mixed multinomial logit.
urn:nbn:de:101:1-2008050531
Keywords: 330